Political capitalism in the digital era: reconstructing the capital–state relation - Filippa Chatzistavrou (Frontiers in Political Science)
This article discusses the role of big tech in becoming an engine of capturing public power. We focus on tech capitalist classes and their determination to capture both the economic benefit and the political decision. First, the article does so by bringing to the fore input from Weber’s political capitalism to explain the linkages between state and tech capitalists as the illustration of a structural dependence where lobbying activities are intensified. Second, pushing further the generally admitted idea of states and markets being co-constitutive allows to broaden the concept of political capitalism to include not only rent seeking, property rights’ issues, and surplus extraction mechanisms but also models of governance. The study suggests that in the case of digital capitalism, property rights on productive resources, originally private while also publicly subsidized, can make big tech not just shapers of common values but also providers of public goods.